Diel patterns and tissue-specificity of environmental responses in fish - Prokkola, Jenni (fi=Turun yliopisto|en=University of Turku|, 2016)
Humans are profoundly changing aquatic environments through climate change and the release of nutrients and chemicals. To understand the effects of these changes on natural populations, knowledge on individuals’ environmental responses is needed. At the molecular level, the environmental responses are partly mediated by chances in messenger RNA and protein levels. In this thesis I study messenger RNA and protein responses to an assortment of environmental stressors in fish. As daily (diel) rhythms are known to be ubiquitous in different tissues, I particularly focus on diel patterns in the responses. The studied species are the three-spined stickleback (Gasterosteus aculeatus L.) and the Arctic char (Salvelinus alpinus L.), both of which have circumpolar distribution in the Northern hemisphere. In the first two studies, three-spined sticklebacks were exposed to both the non-steroidal anti-inflammatory drug diclofenac and low-oxygen conditions (hypoxia), and their responses measured at separate time points in the liver and gills. The results show how the seemingly unrelated environmental stressors, hypoxia and anti-inflammatory drugs, can have harmful combined effects that differ from the effects of each stressor alone. Moreover, both stressors disturbed natural diel patterns in gene expression. In the third study, I studied the responses of three-spined sticklebacks to two test chemicals: one used in hormonal medicine (17α-ethinyl-oestradiol) and one used as a plasticizer and solvent chemical (di-n-butyl phthalate). The results suggest that the phthalate can affect genes related to spermatogenesis in fish testes, while estrogen-mimicking compounds can lead to numerous disturbances in the endocrine system. In the final study, the temperature-dependence of diel rhythms in messenger RNA levels were evaluated in the liver tissue of the Arctic char, a cold-adapted salmonid. The results show that cold acclimation repressed diel rhythms in gene expression compared to warm-acclimated fish, in which the expression of hundreds of genes was rhythmic, suggesting the circadian clock of the Arctic fish species can be sensitive to temperature. Overall, the results of the thesis indicate that fishes’ responses to abiotic factors interact with their diel rhythms, and more studies on the consequences of these interactions are needed to comprehensively understand human impacts on ecosystems.

Ihmistoiminnan tuottamat kasvihuonekaasut sekä kemikaali- ja ravinnepäästöt muuttavat ympäristöä voimakkaasti. Muutosten vaikutusten ymmärtämiseksi tarvitsemme tietoa eri lajien ympäristövasteista. Molekyylitasolla vasteita säätelevät proteiinit, joiden määrä soluissa on osin riippuvainen tuotetun lähetti-RNA:n määrästä. Tässä väitöskirjassa käsittelen eri ympäristömuutosten vaikutuksia kaloihin lähetti-RNA:n määrän ja entsyymiaktiivisuuden tasolla eri kudoksissa. Vuorokausirytmien tiedetään säätelevän monien geenien ilmenemistä, joten keskityin etenkin ajalliseen vaihteluun kalojen ympäristövasteissa. Tutkitut kalalajit olivat lauhkeaan ilmastoon sopeutunut kolmipiikki (Gasterosteus aculeatus L.) ja arktisiin olosuhteisiin sopeutunut nieriä (Salvelinus alpinus L.). Kummatkin lajit elävät laajoilla alueilla pohjoisella pallonpuoliskolla. Kahdessa ensimmäisessä työssä testasin kolmipiikkien vasteita jätevesissä esiintyvälle tulehduskipulääke diklofenaakille ja vähähappisille olosuhteille (hypoksialle). Maksa- ja kiduskudoksista saadut tulokset osoittavat hypoksialla ja diklofenaakilla olevan mahdollisesti haitallisia yhteisvaikutuksia kaloihin, ja että kiduksissa ja maksassa tapahtuvat muutokset voivat olla erisuuntaisia. Sekä diklofenaakin että hypoksian havaittiin myös muuttavan entsyymien luontaista päivärytmiä. Kolmannessa osatyössä tutkin kolmipiikkien vasteita kahdelle hormonitoimintaa häiritseville yhdisteelle, keinotekoiselle estradiolille sekä muoviyhdisteissä käytetylle dibutyyliftalaatille. Havaitsin ftalaatin vaikuttavan siittiöiden toimintaa säätelevien geenien luentaan ja estradiolin estävän useiden steroidihormonien tuotantoa säätelevien geenien ilmenemistä kalojen sukuelimissä. Viimeisessä osatyössä tutkin lämpenemisen vaikutuksia geeniluennan päivärytmiin lohikaloihin kuuluvalla nieriällä. Tulokset osoittivat, että korkeassa lämpötilassa nieriän geenien luenta vaihteli voimakkaasti päivän aikana, mutta viileässä lämpötilassa vaihtelu oli huomaamatonta, mikä viittaa siihen, että arktisten kalojen biologinen kello voi olla herkkä lämpötilamuutoksille. Kokonaisuudessaan väitöskirjan tulokset osoittavat, että meidän on vaikea ennustaa ympäristömuutosten yhteisvaikutuksia luonnon populaatioihin, jos emme ymmärrä ympäristövasteiden ja biologisten rytmien vuorovaikutuksia.